Tear Reservoir Thickness and Vector-Resolved Refractive Outcomes in Indonesian Corneal Ectasia: A Scleral Lens Pilot Study - Anak Agung Ayu Putri Prematura Sri Anasary; Ariesanti Tri Handayani (HM Publisher, 2026)
Background: Corneal ectasia is characterized by high-order aberrations and irregular astigmatism, presenting significant optical challenges. Scleral lenses neutralize these irregularities via a post-lens tear reservoir. However, the precise optical contribution of the tear reservoir thickness itself to residual refractive error remains under-characterized, particularly in Southeast Asian populations where aggressive ectasia phenotypes are common. This study aimed to determine if tear reservoir thickness correlates with residual refractive error using vector analysis. Methods: This retrospective pilot study analyzed 12 eyes of 8 patients with severe corneal ectasia fitted with scleral lenses in Indonesia. Refractive outcomes were converted to Thibos power vectors (M, J0, J45). To account for bilateral eye correlations, linear mixed models (LMM) were employed with Patient ID as a random effect. A theoretical thick-lens model compared predicted versus observed over-refraction. Results: The cohort (mean age 28 ± 10.2 years) achieved significant visual improvement (LogMAR 0.35 to 0.17; p = 0.005). The mean tear reservoir thickness was 263.33 ± 80.92 μm. LMM analysis revealed no statistically significant correlation between fluid thickness and Spherical Equivalent (M) (beta = -0.001, p = 0.72) or Blur Strength (p = 0.68). The theoretical model indicated that residual error was driven by uncorrected posterior corneal astigmatism rather than fluid depth. Conclusion: In this Indonesian cohort, optical efficacy was driven by refractive index matching at the corneal interface, not reservoir thickness. Clinical fitting should prioritize physiological clearance over refractive manipulation.